83.0k views
1 vote
(4x-9)(12x-3) FOIL or double-distribute

2 Answers

2 votes

Answer:

48x^2-120x+27

Explanation:

P.S. - x^2 means x squared.

User Juned Lanja
by
6.0k points
4 votes

Answer:

Simplifying

4x + 9 = 12x + -3

Reorder the terms:

9 + 4x = 12x + -3

Reorder the terms:

9 + 4x = -3 + 12x

Solving

9 + 4x = -3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.

9 + 4x + -12x = -3 + 12x + -12x

Combine like terms: 4x + -12x = -8x

9 + -8x = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0

9 + -8x = -3 + 0

9 + -8x = -3

Add '-9' to each side of the equation.

9 + -9 + -8x = -3 + -9

Combine like terms: 9 + -9 = 0

0 + -8x = -3 + -9

-8x = -3 + -9

Combine like terms: -3 + -9 = -12

-8x = -12

Divide each side by '-8'.

x = 1.5

Simplifying

x = 1.5

Explanation:

User Tez
by
5.7k points